Comparative Analysis of the Mental Readiness of Urban and Rural Students in the Industrial Context - Sarbany, Sarbany; Karyanti, Karyanti; Solikin, Asep; Fatchurrahman, M.; Sulistiawati, Cindy; Hamsiah, Hamsiah; Agang, Yosef (Suluh: Jurnal Bimbingan dan Konseling, 2025)
Background: The transformation of modern industry requires students to be mentally prepared for the workforce; therefore, educational institutions must ensure that character development and psychological resilience are integral components of the learning process. Aim: This study aims to analyze the level of students' mental readiness in facing the industrial world, compare differences in readiness based on regional background, and examine the contribution of character education to the reinforcement of work Readiness. Method: The research employed a descriptive-comparative quantitative approach with a sample of students from urban and rural backgrounds. The measurement instrument used a mental readiness scale encompassing dimensions of self-confidence, resilience, emotional regulation, and adaptability. Results and Discussion: The results indicate that the majority of students fall into the high mental readiness category, with a higher proportion of urban students than rural students. These findings are consistent with the literature, which suggests that differences in access to education, exposure to technology, and social experiences influence individuals' psychological readiness. Conclusions: The study concludes that character education plays a significant role in shaping mental readiness and can be integrated into higher education, industrial guidance, and counseling programs. This research recommends developing character-based counseling interventions and industry practice experiences to strengthen students' readiness to enter the professional world.